Adhesive composition and laminate
Patent Information
- Application Number
- JP2023509205
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-26
- Filing Date
- 2022-03-22
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2042-03-22
AI Technical Summary
【0013】 本発明の接着性組成物における変性ポリオレフィン樹脂は、ポリオレフィン樹脂が、不飽和カルボン酸およびラジカル反応性芳香族化合物によって、所定の変性量に基づいて、変性されている。これにより、この接着性組成物を用いて得られるプライマー層は、ポリオレフィン樹脂からなる基材との密着性、および、ポリオレフィン樹脂よりも極性が高い材料からなる表面層との密着性に優れる。
Smart Images

Figure 0007636520000002 
Figure 0007636520000003 
Figure 0007636520000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition and a laminate. [Background technology]
[0002] Polyolefin resins have been used in various fields such as packaging materials.
[0003] On the other hand, polyolefin resins have low polarity and therefore low adhesiveness to materials that are more polar than polyolefin resins (highly polar materials).
[0004] Therefore, from the viewpoint of improving the adhesiveness of the polyolefin resin, it is known to provide a primer layer between the polyolefin resin and the highly polar material.
[0005] As a material for forming such a primer layer, for example, a modified polyolefin resin obtained by modifying a polyolefin resin with an acid anhydride of an α,β-carboxylic acid and a compound having a benzene ring has been proposed (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2018 / 037849 Summary of the Invention [Problem to be solved by the invention]
[0007] On the other hand, the primer layer is required to have even higher adhesiveness.
[0008] The present invention provides an adhesive composition and a laminate that have excellent adhesion between a substrate made of a polyolefin resin and a surface layer made of a material having a higher polarity than the polyolefin resin, and also have excellent coatability. [Means for solving the problem]
[0009] The present invention [1] is an adhesive composition comprising a modified polyolefin resin, the modified polyolefin resin being a polyolefin resin modified with an unsaturated carboxylic acid and a radical-reactive aromatic compound, the polyolefin resin having a heat of fusion of 10 J / g or less as measured in accordance with JIS K7122, a modification amount of the unsaturated carboxylic acid relative to the modified polyolefin resin being more than 0.5 mass% and less than 5 mass%, and a modification amount of the radical-reactive aromatic compound relative to the modified polyolefin resin being 0.1 mass% or more and less than 3 mass%.
[0010] The present invention [2] includes the adhesive composition according to the above [1], in which the amount of modification of the modified polyolefin resin with the radical reactive aromatic compound is 0.5 mass % or more.
[0011] The present invention [3] is characterized in that the amount of the unsaturated carboxylic acid modified with respect to the modified polyolefin resin is 1.1 mass% or more. the above[ 1 ] or [ 2 ] The adhesive composition according to claim 1,
[0012] The present invention [4] includes a laminate comprising, in order toward one side in a thickness direction, a substrate made of a polyolefin resin, a primer layer made of the adhesive composition described in any one of [1] to [3] above, and a surface layer made of a material having a higher polarity than the polyolefin resin. Effect of the Invention
[0013] The modified polyolefin resin in the adhesive composition of the present invention is a polyolefin resin modified with an unsaturated carboxylic acid and a radically reactive aromatic compound based on a predetermined modification amount, and as a result, a primer layer obtained by using this adhesive composition has excellent adhesion to a substrate made of a polyolefin resin and to a surface layer made of a material having a higher polarity than the polyolefin resin.
[0014] In addition, the polyolefin resin has a heat of fusion within a specific range, which allows the primer layer obtained by using this adhesive composition to have excellent adhesion to a substrate made of a polyolefin resin.
[0015] The laminate of the present invention includes a primer layer made of the adhesive composition of the present invention, and therefore has excellent adhesion between a substrate made of a polyolefin resin and a surface layer made of a material having a higher polarity than the polyolefin resin. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a schematic diagram showing one embodiment of a laminate of the present invention. [Diagram 2] Fig. 2 is a schematic diagram showing one embodiment of the method for producing a laminate of the present invention. Fig. 2A shows a first step of preparing a polyolefin substrate. Fig. 2B shows a second step of disposing a primer layer on one surface in the thickness direction of the polyolefin substrate. Fig. 2C shows a third step of disposing a surface layer on one surface in the thickness direction of the primer layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The adhesive composition includes a modified polyolefin resin.
[0018] The modified polyolefin resin can be obtained by modifying a polyolefin resin with an unsaturated carboxylic acid and a radical-reactive aromatic compound.
[0019] <Polyolefin resin> The polyolefin resin is an olefin polymer containing structural units derived from an olefin.
[0020] Examples of olefins include α-olefins, such as ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-octadecene, and 1-eicosene.
[0021] The olefin is preferably an α-olefin having from 2 to 6 carbon atoms, and more preferably ethylene, propylene, and 1-butene.
[0022] The olefins can be used alone or in combination of two or more kinds. Preferred are a combination of ethylene and propylene, and a combination of ethylene, propylene and 1-butene. In other words, the polyolefin resin is preferably a propylene / ethylene copolymer, or a propylene / 1-butene / ethylene copolymer.
[0023] When the polyolefin resin is a propylene / ethylene copolymer, the content of the propylene-derived structural units relative to the total amount of the propylene-derived structural units and the ethylene-derived structural units (100 mol%) is, for example, 60 mol% or more, preferably 70 mol% or more, and, for example, 90 mol% or less, preferably 80 mol% or less. The content of the ethylene-derived structural units is, for example, 10 mol% or more, preferably 20 mol% or more, and, for example, 40 mol% or less, preferably 30 mol% or less.
[0024] In addition, when the polyolefin resin is a propylene / 1-butene / ethylene copolymer, the content ratio of the propylene-derived structural units relative to the total amount of propylene-derived structural units, 1-butene-derived structural units, and ethylene-derived structural units (100 mol%) is, for example, 50 mol% or more, preferably 60 mol% or more, and, for example, 80 mol% or less, preferably 70 mol% or less. In addition, the content ratio of the 1-butene-derived structural units is, for example, 5 mol% or more, preferably 10 mol% or more, and, for example, 30 mol% or less, preferably 20 mol% or less. In addition, the content ratio of the ethylene-derived structural units is, for example, 10 mol% or more, preferably 20 mol% or more, and, for example, 40 mol% or less, preferably 30 mol% or less.
[0025] The heat of fusion of the polyolefin resin, measured in accordance with JIS K7122, is 10 J / g or less, preferably 5 J / g or less, more preferably 3 J / g or less, and usually 0 J / g or more.
[0026] In addition, if the heat of fusion is equal to or less than the above upper limit, the primer layer 3 (described later) obtained by using this adhesive composition has excellent adhesion to the polyolefin substrate 2 (described later).
[0027] The method for measuring the heat of fusion will be described in detail in the Examples below.
[0028] The melting point of the polyolefin resin is, for example, 50° C. or more, preferably 60° C. or more, more preferably 70° C. or more, and for example, 115° C. or less, preferably 113° C. or less, more preferably 110° C. or less.
[0029] Alternatively, the material may be amorphous and contain no polyolefin resin.
[0030] The method for measuring the melting point will be described in detail in the Examples below.
[0031] The polystyrene-equivalent weight average molecular weight of the polyolefin resin measured by gel permeation chromatography (GPC) is, for example, 40,000 or more, preferably 50,000 or more, more preferably 55,000 or more, and for example, 500,000 or less, preferably 400,000 or less, more preferably 380,000 or less.
[0032] The method for measuring the weight average molecular weight will be described in detail in the Examples below.
[0033] The polyolefin resin can be obtained by polymerizing an olefin by a known method. In the polymerization, a metallocene catalyst can be added, if necessary.
[0034] <Unsaturated carboxylic acid> Examples of unsaturated carboxylic acids include unsaturated carboxylic acids having 3 to 8 carbon atoms. Examples of unsaturated carboxylic acids having 3 to 8 carbon atoms include monobasic acids and dibasic acids. Examples of monobasic acids include (meth)acrylic acid (acrylic acid and / or methacrylic acid), crotonic acid, and isocrotonic acid. Examples of dibasic acids include maleic acid, fumaric acid, itaconic acid, citraconic acid, mesaconic acid, glutaconic acid, allylsuccinic acid, nadic acid, methylnadic acid, tetrahydrofumaric acid, and methylhexahydrophthalic acid.
[0035] Furthermore, the unsaturated carboxylic acid may be an acid anhydride of the above-mentioned unsaturated carboxylic acid.
[0036] As the unsaturated carboxylic acid, preferably, an acid anhydride of an unsaturated carboxylic acid is used, more preferably, an acid anhydride of a dibasic acid is used, and further preferably, maleic anhydride is used.
[0037] The unsaturated carboxylic acids can be used alone or in combination of two or more kinds.
[0038] The amount of unsaturated carboxylic acid modified in the modified polyolefin resin exceeds 0.5% by mass, preferably 1.1% by mass or more, and is less than 5% by mass, preferably 3% by mass or less, and more preferably 2% by mass or less.
[0039] When the modification amount is equal to or greater than the lower limit, the primer layer 3 (described later) obtained by using this adhesive composition has excellent adhesion to the surface layer 4 (described later) and to the polyolefin substrate 2 (described later), and is particularly excellent in adhesion to the surface layer 4 (described later). Furthermore, when the modification amount is 1.1% by mass or more, the adhesion is even more excellent.
[0040] Furthermore, when the modification amount is equal to or less than the upper limit, the primer layer 3 (described later) obtained using this adhesive composition has excellent adhesion to the surface layer 4 (described later) and to the polyolefin substrate 2 (described later), and is particularly excellent in adhesion to the polyolefin substrate 2 (described later).
[0041] The amount of modification can be determined, for example, from the blending ratio of each component when preparing the modified polyolefin resin. 1 This can be confirmed by known means such as H-NMR measurement.
[0042] <Radical reactive aromatic compounds> A radically reactive aromatic compound is a compound that has both a radical addition site and an aromatic ring.
[0043] Examples of the radically reactive aromatic compound include a radically polymerizable double bond-containing aromatic compound and a radically reactive aromatic hydrocarbon.
[0044] A radically polymerizable double bond-containing aromatic compound is a compound that has both a radically polymerizable double bond and an aromatic ring.
[0045] Examples of the aromatic compound containing a radical polymerizable double bond include aromatic vinyl compounds and aromatic ring-containing (meth)acrylic acid esters. Examples of the aromatic vinyl compounds include styrene, α-methylstyrene (2-phenylpropylene), 2-phenylbutene, 3-phenylpropylene, divinylbenzene, 1-vinylnaphthalene, p-methylstyrene, m-methylstyrene, o-methylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, 3-methyl-5-ethylstyrene, p-tert-butylstyrene, p-sec-butylstyrene, p-chlorostyrene, p-vinylbenzoic acid, p-vinylbenzoic acid esters, and vinyl benzoate. Examples of the aromatic ring-containing (meth)acrylic acid esters include phenyl (meth)acrylate, benzyl (meth)acrylate, phenoxyethyl (meth)acrylate, and trityl (meth)acrylate.
[0046] Radical reactive aromatic hydrocarbons include, for example, toluene, xylene, and ethylbenzene.
[0047] The radically reactive aromatic compound is preferably a radically polymerizable double bond-containing aromatic compound, more preferably an aromatic vinyl compound, and even more preferably styrene.
[0048] In addition, the modification amount of the radical reactive aromatic compound in the modified polyolefin resin is 0.1 mass% or more, preferably 0.5 mass% or more, more preferably 1.0 mass% or more, and for example, less than 3 mass%, preferably 2 mass% or less, more preferably 1.5 mass% or less, and even more preferably 1.1 mass% or less.
[0049] When the modification amount is equal to or greater than the lower limit, the primer layer 3 (described later) obtained by using this adhesive composition has excellent adhesion to the polyolefin substrate 2 (described later). In particular, when the modification amount is equal to or greater than 0.5% by mass, the adhesion is even more excellent.
[0050] When the modification amount is equal to or less than the upper limit, an increase in viscosity of the adhesive composition can be suppressed, and the adhesive composition has excellent coatability (specifically, spray coatability).
[0051] The amount of modification can be determined, for example, from the blending ratio of each component when preparing the modified polyolefin resin. 1 This can be confirmed by known means such as H-NMR measurement.
[0052] <Preparation of modified polyolefin resin> The modified polyolefin resin can be obtained by modifying a polyolefin resin with an unsaturated carboxylic acid and a radical-reactive aromatic compound.
[0053] Specifically, the polyolefin resin is obtained by polymerizing an unsaturated carboxylic acid and a radical-reactive aromatic compound in the presence of a polyolefin resin, whereby the polyolefin resin is graft-modified with the unsaturated carboxylic acid and the radical-reactive aromatic compound.
[0054] The reaction temperature is, for example, 50° C. or more, preferably 80° C. or more, and, for example, 250° C. or less. The reaction time is, for example, 1 minute or more and 10 hours or less.
[0055] In the above reaction, a radical polymerization initiator is added in an appropriate ratio, if necessary.
[0056] Examples of the radical polymerization initiator include organic peroxides such as benzoyl peroxide, dichlorobenzoyl peroxide, dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(peroxybenzoate)hexyne-3, 1,4-bis(tert-butylperoxyisopropyl)benzene, lauroyl peroxide, tert-butyl peracetate, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, tert-butyl benzoate, tert-butyl perphenyl acetate, tert-butyl perisobutyrate, tert-butyl per-sec-octoate, tert-butyl perpivalate, cumyl perpivalate, and tert-butyl perdiethyl acetate; and azo compounds such as azobis-isobutylnitrile and dimethylazoisobutylnitrile.
[0057] As the radical polymerization initiator, dialkyl peroxides such as dicumyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexyne-3, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, and 1,4-bis(tert-butylperoxyisopropyl)benzene are preferred.
[0058] The above reaction is carried out in the presence of a solvent or without a solvent.
[0059] As the solvent, a known solvent can be selected.
[0060] In this way, a modified polyolefin resin is obtained. When the reaction is carried out in the presence of a solvent, the obtained modified polyolefin resin is prepared as a varnish.
[0061] The melting point of the modified polyolefin resin is, for example, 50°C or more, preferably 60°C or more, more preferably 70°C or more, and for example, 115°C or less, preferably 113°C or less, more preferably 110°C or less.
[0062] Alternatively, the material may be amorphous and not contain a modified polyolefin resin.
[0063] The method for measuring the melting point will be described in detail in the Examples below.
[0064] The weight average molecular weight of the modified polyolefin resin, measured by gel permeation chromatography (GPC) in terms of polystyrene, is, for example, 40,000 or more, preferably 50,000 or more, more preferably 55,000 or more, and for example, 500,000 or less, preferably 400,000 or less, more preferably 380,000 or less.
[0065] The method for measuring the weight average molecular weight will be described in detail in the Examples below.
[0066] The adhesive composition contains the above-mentioned modified polyolefin resin and, if necessary, a solvent.
[0067] When the adhesive composition contains a solvent, the solids concentration of the modified polyolefin resin is, for example, 1.0 mass % or more, preferably 3.0 mass % or more, and for example, 30 mass % or less, preferably 20 mass % or less.
[0068] As will be described in detail later, a primer layer 3 (described later) obtained by using the adhesive composition has excellent adhesion to both a polyolefin substrate 2 (described later) and a surface layer 4 (described later). Therefore, the adhesive composition is suitably used for forming a primer layer disposed between the polyolefin substrate 2 (described later) and the surface layer 4 (described later).
[0069] Hereinafter, the laminate 1 having a primer layer 3 (described below) obtained by using the adhesive composition will be described in detail.
[0070] <Laminate> One embodiment of the laminate of the present invention will be described with reference to FIG.
[0071] In Fig. 1, the up-down direction of the paper is the up-down direction (thickness direction), the upper side of the paper is the upper side (one side in the thickness direction), and the lower side of the paper is the lower side (the other side in the thickness direction). The left-right direction and the depth direction of the paper are surface directions perpendicular to the up-down direction. Specifically, they follow the directional arrows in each figure.
[0072] The laminate 1 has a film shape (including a sheet shape) with a predetermined thickness, as shown in Fig. 1. The laminate 1 extends in a plane direction perpendicular to the thickness direction. The laminate 1 has a flat upper surface and a flat lower surface.
[0073] The laminate 1 includes a polyolefin substrate 2, a primer layer 3, and a surface layer 4, arranged in this order toward one side in the thickness direction. Specifically, the laminate 1 includes a polyolefin substrate 2, a primer layer 3 disposed directly on the upper surface (one surface in the thickness direction) of the polyolefin substrate 2, and a surface layer 4 disposed directly on the upper surface (one surface in the thickness direction) of the primer layer 3.
[0074] <Polyolefin base material> The polyolefin substrate 2 has a film shape. The polyolefin substrate 2 is disposed over the entire lower surface of the primer layer 3 so as to be in contact with the lower surface of the primer layer 3.
[0075] The polyolefin substrate 2 is made of a polyolefin resin.
[0076] Examples of the polyolefin resin include the polyolefin resins exemplified in the adhesive composition described above.
[0077] <Primer layer> The primer layer 3 has a film shape and is disposed over the entire lower surface of the surface layer 4 so as to be in contact with the lower surface of the surface layer 4.
[0078] The primer layer 3 is formed from an adhesive composition.
[0079] The primer layer 3, which will be described in detail later, is obtained by applying an adhesive composition to one surface in the thickness direction of the polyolefin substrate 2.
[0080] The thickness of the primer layer 3 is, for example, 1 μm or more and, for example, 5 μm or less.
[0081] <Surface layer> The surface layer 4 has a film shape. The surface layer 4 is disposed over the entire upper surface of the primer layer 3 so as to be in contact with the upper surface of the primer layer 3. The surface layer 4 is the uppermost layer of the laminate 1.
[0082] The surface layer 4 is made of a material having a higher polarity than polyolefin resin (high polarity material).
[0083] Such highly polar materials include, for example, resins having ether bonds, ester bonds, amide bonds, imide bonds, and urethane bonds, specifically, acrylic resins, polyamide resins, polyimide resins, polyurethane resins, and vinyl chloride-vinyl acetate copolymer resins, and preferably, acrylic resins and vinyl chloride-vinyl acetate copolymer resins.
[0084] The surface layer 4 has a thickness of, for example, 6 μm or more and, for example, 20 μm or less.
[0085] <Method of manufacturing laminate> The method for manufacturing the laminate 1 includes a first step of preparing a polyolefin substrate 2, a second step of disposing a primer layer 3 on one thickness-wise surface of the polyolefin substrate 2, and a third step of disposing a surface layer 4 on one thickness-wise surface of the primer layer 3.
[0086] In the first step, a polyolefin substrate 2 is prepared as shown in FIG. 2A.
[0087] In the second step, as shown in FIG. 2B, a primer layer 3 is disposed on one surface in the thickness direction of the polyolefin substrate 2.
[0088] To dispose the primer layer 3 on one surface in the thickness direction of the polyolefin substrate 2, the above adhesive composition (varnish of modified polyolefin resin) is applied to one surface in the thickness direction of the polyolefin substrate 2, and dried as necessary. In this way, the primer layer 3 is disposed (formed) on one surface in the thickness direction of the polyolefin substrate 2.
[0089] The coating method is not particularly limited, but from the viewpoint of productivity, spray coating is preferable.
[0090] The drying conditions are not particularly limited as long as the volatile matter such as the organic solvent contained in the adhesive composition is evaporated, but the drying temperature is, for example, 200° C. or less, preferably 150° C. or less, and, for example, 10° C. or more. The drying time is, for example, 3 seconds or more, preferably 1 minute or more, and, for example, 1 hour or less.
[0091] In the third step, as shown in FIG. 2C, a surface layer 4 is disposed on one surface in the thickness direction of the primer layer 3.
[0092] The material of the surface layer 4 is applied to one surface in the thickness direction of the primer layer 3, and dried as necessary. In this way, the surface layer 4 is disposed (formed) on one surface of the primer layer 3 in the thickness direction.
[0093] The drying conditions are not particularly limited as long as the volatile matter such as the organic solvent contained in the material of the surface layer 4 is evaporated, and the drying temperature is, for example, 200° C. or less, preferably 150° C. or less, and for example, 10° C. or more. The drying time is, for example, 3 seconds or more, preferably 1 minute or more, and for example, 1 hour or less.
[0094] In this manner, the laminate 1 is obtained.
[0095] <Action and effect> The modified polyolefin resin in the adhesive composition is a polyolefin resin modified with an unsaturated carboxylic acid and a radically reactive aromatic compound at a predetermined modification amount, so that the primer layer 3 obtained by using this adhesive composition has excellent adhesion to the polyolefin substrate 2 and to the surface layer 4.
[0096] Specifically, increasing the amount of modification of the unsaturated carboxylic acid increases the polarity of the primer layer 3, improving adhesion to the surface layer 4, which has a relatively high polarity, while tending to decrease adhesion to the polyolefin substrate 2, which has a relatively low polarity.
[0097] Furthermore, when the amount of modification with the radical reactive aromatic compound is increased, the adhesion to the polyolefin substrate 2 improves, but the coatability tends to decrease.
[0098] In the adhesive composition, both the modification amount of the unsaturated carboxylic acid and the modification amount of the radical reactive aromatic compound are adjusted to a predetermined range. This improves the applicability of the adhesive composition, and the primer layer 3 obtained by using this adhesive composition has excellent adhesion to the polyolefin substrate 2 and to the surface layer 4. As a result, the polyolefin substrate 2, which has a relatively low polarity, and the surface layer 4, which has a relatively high polarity, can be bonded via the primer layer 3.
[0099] In addition, the polyolefin resin has a heat of fusion within a specific range, which allows the primer layer 3 obtained by using this adhesive composition to have excellent adhesion to the polyolefin substrate 2.
[0100] On the other hand, the modified polyolefin resin of Patent Document 1 is obtained by modifying a polyolefin resin with an acid anhydride of an α,β-carboxylic acid (specifically, maleic anhydride) and a compound having a benzene ring (specifically, benzylamine). More specifically, the polyolefin resin is first graft-modified with maleic anhydride. Then, the carboxyl group of the maleic anhydride, which has been ring-opened by the modification, is reacted with the amino group of the benzylamine. In this way, the benzylamine inhibits adhesion to the polyolefin substrate 2.
[0101] In contrast, in the modified polyolefin resin of the present invention, both the unsaturated carboxylic acid and the radical-reactive aromatic compound are graft-modified onto the polyolefin resin by a radical reaction.
[0102] In other words, the modified polyolefin resin of the present invention is one in which both an unsaturated carboxylic acid and a radically reactive aromatic compound are graft-modified to one molecule of polyolefin resin, and is distinguished from a mixture in which one molecule of polyolefin resin is graft-modified to an unsaturated carboxylic acid and one molecule of polyolefin resin is graft-modified to a radically reactive aromatic compound. This allows the radically reactive aromatic compound to be efficiently introduced into the polyolefin resin, improving the adhesion to the polyolefin substrate 2.
[0103] The laminate 1 also includes a primer layer 3 made of the above-mentioned adhesive composition, so that the adhesion between the polyolefin substrate 2 and the surface layer 4 is excellent.
[0104] The laminate 1 is suitable for use in various fields such as packaging materials.
[0105] In the above description, the surface layer 4 is a single layer. On the other hand, the surface layer 4 may be a multi-layer (for example, two or more layers, preferably two or three layers).
[0106] In the above description, the polyolefin substrate 2 is in the form of a film, but the shape of the polyolefin substrate 2 is not limited to this and may be, for example, in the form of a plate. EXAMPLES
[0107] Next, the present invention will be described based on examples and comparative examples, but the present invention is not limited to the following examples. Note that "parts" and "%" are based on mass unless otherwise specified. In addition, the specific numerical values of the blending ratio (content ratio), physical property values, parameters, etc. used in the following description can be replaced with the upper limit value (numerical value defined as "less than or equal to" or "less than") or lower limit value (numerical value defined as "more than or equal to" or "exceeding") of the corresponding blending ratio (content ratio), physical property values, parameters, etc. described in the above "Form for carrying out the invention".
[0108] 1. Preparation of adhesive composition Example 1 Into a 1.0 L autoclave equipped with a stirrer were placed 100 parts by mass of a propylene-ethylene copolymer (PER) containing 79 mol % propylene units and 21 mol % ethylene units and 516 parts by mass of butyl acetate, and the temperature was raised to 145°C with stirring until the propylene-ethylene copolymer was completely dissolved.
[0109] Then, while the solution was kept at 145°C, 6 parts by mass of maleic anhydride, 1.5 parts by mass of styrene, and 3.6 parts by mass of di-tert-butyl peroxide were dropped over 6 hours under stirring. After the dropwise addition was completed, the reaction was carried out by stirring at 145°C for another 3 hours. Next, the obtained solution was cooled to 80°C and then diluted with 774 parts by mass of methylcyclohexane. Next, the solution was cooled to room temperature and diluted with 1290 parts by mass of toluene to a solid content of 4%. As a result, an adhesive composition containing a modified polyolefin resin was obtained.
[0110] Examples 2 to 4 and Comparative Examples 1 to 6 According to the same procedure as in Example 1, an adhesive composition containing a modified polyolefin resin was obtained.
[0111] However, the formulation was changed according to Table 1.
[0112] In Example 4, a propylene-butene-ethylene copolymer (PBER) containing 66 mol % of propylene units, 13 mol % of butene units, and 21 mol % of ethylene units was used.
[0113] In Comparative Example 5, a propylene-butene-ethylene copolymer (PBER) containing 63 mol % of propylene units, 23 mol % of butene units, and 14 mol % of ethylene units was used.
[0114] In Comparative Example 6, a propylene-ethylene copolymer (PER) containing 85 mol % of propylene units and 15 mol % of ethylene units was used.
[0115] Comparative Example 7 A 1.0 L autoclave equipped with a stirrer was charged with 50 parts by mass of a propylene-ethylene copolymer having 79 mol % of propylene units and 21 mol % of ethylene units and 261.6 parts by mass of butyl acetate, and the mixture was heated to 145°C with stirring until the propylene-ethylene polymer was completely dissolved.
[0116] Thereafter, while keeping the solution at 145°C, 6 parts by mass of maleic anhydride and 3.6 parts by mass of di-tert-butyl peroxide were added dropwise over 6 hours under stirring. After the completion of the dropwise addition, the reaction was carried out by stirring at 145°C for another 3 hours. The temperature of the resulting solution was then lowered to 80°C, and the solution was diluted with 392.4 parts by mass of methylcyclohexane. This was cooled to room temperature to obtain solution X. Next, the same operation as for solution X was carried out, except that 6 parts by mass of maleic anhydride was replaced by 3 parts by mass of styrene, to obtain solution Y.
[0117] Solution X and solution Y were mixed at room temperature, and then the mixture was diluted with 1,308 parts by mass of toluene to a solid content of 4%, to obtain an adhesive composition.
[0118] Comparative Example 8 A 1.0 L autoclave equipped with a stirrer was charged with 100 parts by mass of a propylene-ethylene copolymer having 79 mol % of propylene units and 21 mol % of ethylene units and 537.6 parts by mass of butyl acetate, and the mixture was heated to 145°C with stirring until the propylene-ethylene copolymer was completely dissolved.
[0119] Next, while keeping this solution at 145°C, 6 parts by mass of maleic anhydride and 3.6 parts by mass of di-tert-butyl peroxide were added dropwise over 6 hours under stirring. After the dropwise addition was completed, the mixture was further stirred at 145°C for 3 hours to carry out a post-reaction. The obtained solution was cooled to 135°C, and then 6 parts by mass of benzylamine was added and stirred for another 2 hours. The solution was cooled to 80°C and diluted with 806.4 parts by mass of methylcyclohexane. This was cooled to room temperature and diluted with 1344 parts by mass of toluene to a solid content of 4%, to obtain an adhesive composition.
[0120] 2. Measurement of heat of fusion For the polyolefin resin used in each of the Examples and Comparative Examples, the heat of fusion was determined using a differential scanning calorimeter (manufactured by TA Instruments; DSC-Q1000). The temperature was raised from 30°C to 180°C at 10°C / min, then lowered to 0°C at 10°C / min, and then raised again to 150°C at 10°C / min. The melting point and heat of fusion were determined from the thermogram taken during the second temperature rise in accordance with JIS K 7122. The results are shown in Table 1.
[0121] 3. Measurement of the amount of denaturation The amount of unsaturated carboxylic acid modified to the polyolefin resin and the amount of radical reactive aromatic compound modified to the polyolefin resin were determined based on the following conditions: 1 The results were measured using H-NMR, and are shown in Table 1. [Measurement conditions] Equipment: JEOL Ltd. ECX400 nuclear magnetic resonance spectrometer Solvent: Deuterated orthodichlorobenzene Sample concentration: 20mg / 0.6mL Measurement temperature: 120℃ Observation nucleus: 1H (400MHz) Sequence: Single Pulse Pulse width: 5.12μsec (45° pulse) Repeat time: 7.0 seconds Number of times: 500 or more
[0122] The reference chemical shift was set to 0 ppm for hydrogen in tetramethylsilane (note that the same results can be obtained by setting the peak derived from the residual hydrogen in deuterated orthodichlorobenzene at 7.10 ppm as the reference value for the chemical shift). Peaks such as 1H derived from functional group-containing compounds were assigned by the usual method.
[0123] 4. Melting Point Measurement The melting points of the polyolefin resins and modified polyolefin resins used in each example were measured. Specifically, using a differential scanning calorimeter (manufactured by TA Instruments; DSC-Q1000), the melting points were obtained according to JIS K7122 from the thermogram obtained during the second heating process, in which the temperature was raised from 25°C to 200°C at 10°C / min, then held at 200°C for 3 minutes, lowered to 0°C at 10°C / min, and then raised to 200°C at 10°C / min again. The results are shown in Table 1.
[0124] 5.Weight average molecular weight The weight average molecular weight of the polyolefin resin used in each Example and the modified polyolefin resin used in each Example was measured. Specifically, the weight average molecular weight was measured based on the GPC method under the following measurement conditions. The results are shown in Table 1. Detector: Shimadzu Corporation; C-R4A Column: TSKG 6000H-TSKG 4000H-TSKG 3000H-TSKG 2000H (manufactured by Tosoh Corporation) move phase :Tetrahydrofuran Column temperature: 40℃ Flow rate: 0.8ml / min The Mw was calculated using a calibration curve prepared from monodisperse standard polystyrene.
[0125] 6. Manufacturing of Laminates [Production of Laminate A] <1st process> A polypropylene plate was prepared.
[0126] <Second process> The adhesive composition of each Example and Comparative Example was spray-coated onto one surface in the thickness direction of a polypropylene plate, and dried for 2 minutes at 60° C. This resulted in a primer layer having a thickness of 2 μm to 3 μm.
[0127] <3rd process> An acrylic paint was sprayed onto one surface in the thickness direction of the primer layer and dried at 60° C. for 3 minutes. The acrylic paint was then cured by UV irradiation. This formed a surface layer with a thickness of 10 μm to 15 μm. Laminate A was produced in this manner.
[0128] [Manufacture of laminate B] Laminate B was produced according to the same procedure as for laminate A.
[0129] However, the third step was changed as follows.
[0130] A paint made of vinyl chloride-vinyl acetate copolymer resin was sprayed onto one surface in the thickness direction of the primer layer, and dried at 60°C for 3 minutes. This formed a first surface layer with a thickness of 5 μm to 6 μm. Next, an acrylic paint was sprayed onto one surface in the thickness direction of this surface layer, and dried at 60°C for 3 minutes. The acrylic paint was then cured by UV irradiation. This formed a second surface layer with a thickness of 10 μm to 15 μm. In this manner, laminate B was produced.
[0131] 7. Evaluation [Adhesion] In laminates A and B of each example and each comparative example, the surface layer was cut into a checkerboard pattern (2 mm intervals, 100 squares), and a peel test was performed using a polypropylene plate or cellophane adhesive tape of the surface layer. The adhesion was evaluated based on the adhesion rate (the number of squares remaining on the substrate).
[0132] Specifically, for the adhesion between polypropylene And and the primer layer (PP adhesion), the adhesion between the surface layer made of an acrylic paint and the primer layer (acrylic adhesion), and the adhesion between the surface layer made of a vinyl chloride-vinyl acetate copolymer resin and the primer layer (vinyl chloride-vinyl acetate copolymer resin adhesion), the evaluation was carried out based on the following criteria. Note that for Comparative Example 4, since the adhesive composition could not be spray-coated, the evaluation of adhesion was not performed.
[0133] <PP Adhesion> For laminates A and B of each example and each comparative example, the adhesion rate between the propylene plate and the primer layer was evaluated by a checkerboard test, and the PP adhesion was judged according to the following criteria. The results are shown in Table 1. 〇: The average adhesion rate was 100. △: The average adhesion rate was less than 100 and 90 or more. ×: The average adhesion rate was less than 90.
[0134] <Acrylic Adhesion> For laminate A of each example and each comparative example, the adhesion rate between the primer layer and the surface layer (acrylic layer) was evaluated by a checkerboard test, and the acrylic adhesion was judged according to the following criteria. The results are shown in Table 1. 〇: The adhesion rate was 100. △: The adhesion rate was less than 100 and 90 or more. ×: The adhesion rate was less than 90.
[0135] <Vinyl Chloride-Vinyl Acetate Copolymer Resin Adhesion> For each of the laminates B in the Examples and Comparative Examples, the adhesion rate between the primer layer and the surface layer (vinyl chloride-vinyl acetate copolymer resin layer) was evaluated by a cross-cut adhesion test, and the vinyl chloride-vinyl acetate copolymer resin adhesion was evaluated according to the following criteria. The results are shown in Table 1. ◯: The adhesion rate was 100. △: The adhesion rate was less than 100 and 90 or more. ×: The adhesion rate was less than 90%.
[0136] [Spray suitability] For each of the adhesive compositions of the Examples and Comparative Examples, the B-type viscosity was measured, and the spray suitability was evaluated according to the following criteria. Good: Viscosity was less than 40 mPa s. It was judged that spray painting was possible. ×: Viscosity was 40 mPa·s or more. It was determined that spray painting was not possible.
[0137] [Table 1]
[0138] The above invention is provided as an exemplary embodiment of the present invention, but this is merely an example and should not be interpreted as being limited. Modifications of the present invention that are obvious to those skilled in the art are included in the scope of the following claims. [Industrial Applicability]
[0139] The adhesive composition and laminate of the present invention can be suitably used, for example, as a packaging material. [Explanation of symbols]
[0140] 1. Laminate 2 Base material 3 Primer layer 4 Surface layer
Claims
1. An adhesive composition comprising a modified polyolefin resin and a solvent, The modified polyolefin resin is obtained by modifying a polyolefin resin with an unsaturated carboxylic acid and a radical reactive aromatic compound, The polyolefin resin has a heat of fusion of 10 J / g or less as measured in accordance with JIS K7122; the amount of the unsaturated carboxylic acid modified with respect to the modified polyolefin resin is more than 0.5% by mass and is not more than 2.0% by mass; the amount of modification of the radical reactive aromatic compound with respect to the modified polyolefin resin is 0.1% by mass or more and 1.0% by mass or less; In the adhesive composition, a solid content concentration of the modified polyolefin resin is 1.0 mass % or more and 30 mass % or less.
2. 2. The adhesive composition according to claim 1, wherein the modified polyolefin resin has a modification amount of the radical reactive aromatic compound of 0.5 mass % or more.
3. 2. The adhesive composition according to claim 1, wherein the amount of the unsaturated carboxylic acid modified with respect to the modified polyolefin resin is 1.1 mass % or more.
4. A substrate made of a polyolefin resin; A primer layer comprising a dried product of the adhesive composition according to claim 1; a surface layer made of a material having a higher polarity than the polyolefin resin, the surface layer being disposed in that order toward one side in the thickness direction.
Citation Information
Patent Citations
Modified polyolefin composition and its use
JP2001139642A
Process for production of modified propylene polymer and modified propylene polymer produced by the process
JP2009114462A
Laminated adhesive film for use in insert molding
WO2012060311A1
Modified polyolefin-based resin
WO2018037849A1